Nischarin Is Not the Functional I1 Imidazoline Receptor Involved in Blood Pressure Regulation. Issue 2 (February 2022) - Arnoux, Alizée; Aubertin, Gaëlle; Da Silva, Sylvia; Weiss, Maud; Bousquet, Pascal; Monassier, Laurent; Niederhoffer, Nathalie
Abstract: Imidazoline receptor antisera selected/Nischarin was proposed several years ago as the functional entity for the I1 medullary receptors (I1 Rs) targeted, together with α2 -adrenoceptors, by the centrally acting antihypertensive drugs, such as clonidine. The objective of this study was to test this assumption using a pyrroline analog of clonidine, LNP599, which, unlike clonidine and related compounds, displays high selectivity toward I1 Rs. Cardiovascular effects of LNP599 (3 mg/kg intravenous) were evaluated in anesthetized, artificially ventilated nischarin mutant rats expressing a truncated form of nischarin lacking the putative imidazoline binding site. LNP599 induced a rapid and pronounced fall in arterial blood pressure in wild-type animals (−42.7% ± 11.0% after 15 minutes), associated with a ≈30% heart rate reduction. Similar effects were obtained in homozygous and heterozygous nischarin mutant rats. The observation that the hypotensive response to I1 R activation is not affected by the absence of the putative imidazoline binding site on nischarin strongly suggests that nischarin cannot be regarded as the functional I1 R. Carbohydrate regulation was improved in nischarin mutant rats, further supporting the conclusion that nischarin and I1 R are 2 distinct molecular entities.